Effect of sea buckthorn (Hippophae rhamnoides) on kidney and of Pontastacus leptodactylustesticular damage, sperm quality and expression of Irisin and Asprosin in Streptozotocin-Induced diabetic rats - Pekince-Ozoner, Merve; Timurkaan, Sema; Gur, Fatih Mehmet; Tarakci-Gencer, Berrin; Eroksuz, Hatice; Gungor, Ibrahim Halil (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
T T In recent years, many antioxidants have been used against hyperglycemiaand oxidative damageindiabetes. The methoate (DM ) pe ticide is o e ofthe hemicals us to purpose of thisstudyis to investigate the protective effects otectsome agr cultural areasfrom harmfu organism DMT ofSea buckthorn (Hippophaerhamnoides) against adverse sidues released irectly or indirectly to the envir nment ause serious problems n nature DMT residues mixed with t e effects of diabetes on testicular and renal tissues. A total of 39 male Sprague-Dawley rats were assigned to 5 groups as quatic e vironm t adve selyffect aquatic o ganisms and follows: control, citrate, SBT, diabetes, and diabetes+SBT. Diabetesinductionwas made by streptozotocin (50mg/kg is effectAs carried to humans t ro gh the food chain n this udy,Aoxidative stesresponssinuced byDMTpesticidein intraperitonally) to diabetes and diabetes+SBT group. SBT oil was administered to SBTweeandinvestigateddiabetes+SBTFothisgrouppurpose,(50mg/ xidativestrssandantioxdatparam te sThiobarbituric cid kg/48h by oral gavage). At the end of study, testicular and kidney samples for histochemical and immunohistochemical act ve substances TBARS) Glutathione (GSH) Superoxide smutase (SOD), cata ase (CAT) a d glutathione peroxidase examinations, serum samples for biochemical examinations and sperm samples for spermatogenic examinations were collected. The results of the analysis showed that SBT reduced PX) caus d by dimet oate (DMT) pesticide inbody weight loss and loweredbloodglucose levels by reducing 17.5, 35, and 70 mg L concentrations at 24 and 96 hours ere investigatedResults weredetermned usingELISA kits. the harmful effects of diabetes-induced oxidative stress. When serum TAS and TOS levels were evaluated, it was determined that TAS level was the highest in the SBT group and TAS ereo served be ween decreases ATnd GPx activities a d level increased in the diabetes + SBT group compared to creases in TBARS evels SPSS 24 0 package progr m one w y diabetes and the other groups. While TOS level increased in the diabetes group, it decreased in the diabetes+SBT group. NOVA (Duncan 0.05) was u ed in the evaluation of biochemical SBT also increased sperm density and motility and reduced nalyzes. AsAa result, it was determi ed that DMT caused oxidative total abnormality (head-tail) in diabetic rats. In SBT-treated ressformatioinand caused changes n enzyme diabetic rats, histopathological changes during the course of ctvties. diabetes significantly reduced. In addition, decreased irisin expression in renal tissue and decreased irisin and asprosin ey words: Dimethoate , oxidative expression in testicular tissue in the diabetes group were significantly normalizedin thediabetes+SBT group. In this s ress,antioxdant, bomarkers study, it was found that the application of SBT oil significantly prevented hyperglycemia and oxidative stress in diabetes, and protected testicular and renal tissues from the functional and histopathological changes in these organs caused by hyperglycemia and oxidative stress in diabetic animals. These results showed that SBT oil was an effective nutritional supplement that can be used to protect against the adverse effects of diabetes.
Keywords: Asprosin; diabetes; Irisin; oxidative Stress; sea buckthorn; sperm quality